Leadership and Organizational Outcomes 2015
DOI: 10.1007/978-3-319-14908-0_4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership on Organizational Commitment

Abstract: The effect of leadership on organizational commitment was examined in this meta-analysis study. A total of 420 research studies were collected as a result of the review activity, out of which 202 were included in the meta-analysis. The 202 research studies were compiled to obtain a sample group size of 63,753 subjects. The analysis results of the random effect model showed that leadership has a medium-level positive effect on organizational commitment. Of the moderators identified, such as sample group/sector,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…This can be interpreted that the more effective a leader in this case is the principal, the teacher will increase commitment to the organization. This is in line with the research results of Zahra (2015), Oztekin, Isci, and Karadag (2015), Sabir, Sohail, and Khan (2011), Fasola. Adeyemi, and Olowe (2013) who also concluded that leadership influences organizational commitment.…”
Section: H1: There Is a Positive Direct Effect Of Leadership Effectivsupporting
confidence: 92%
“…This can be interpreted that the more effective a leader in this case is the principal, the teacher will increase commitment to the organization. This is in line with the research results of Zahra (2015), Oztekin, Isci, and Karadag (2015), Sabir, Sohail, and Khan (2011), Fasola. Adeyemi, and Olowe (2013) who also concluded that leadership influences organizational commitment.…”
Section: H1: There Is a Positive Direct Effect Of Leadership Effectivsupporting
confidence: 92%
“…Principals do not have extensive managerial or leadership role. Mainly, they act as administrators and ensure centrally formulated educational policy (Koutouzis, Manolis., 2017).Due to summarize, normative commitment is defined as the employees' desire to stay in an organization due to ethical reasons, by which they increase the probability of the organization's continuation (Oztekin, Ozge, Sabiha Isci, 2017).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Organizations need to develop and enhance their knowledge about the main organization component, namely human resources (HR) (Avolio et al, 2004;Luthans et al, 2021;Rohman et al, 2022;Turulja & Bajgoric, 2018). There is a need for changes in HR function, which previously served as an implementation staff, to transform into strategic partners and agents of change (Adamik, 2019;Majeed et al, 2017;Öztekin et al, 2015). Besides the resulting output being highly beneficial for an industry, maximum results can be achieved when employees no longer rely only on their skills, but enhance the function of understanding their own potential, their families, and society, to increase added value in the standard of living (Rohman et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%